Electrochromic behavior of fac-tricarbonyl rhenium complexes. (16th December 2021) - Zhou, Qian-hua; Pan, Ming-yue; He, Qi; Tang, Qian; Chow, Cheuk-fai; Gong, Cheng-bin
Abstract : Tricarbonyl rhenium complex shows good electrochromic performance with a colored stage of green, rapid response and good switching stability. Abstract : This paper aims to investigate the electrochromic properties of tricarbonyl rhenium complexes. Using 4, 7-diphenylphenanthroline (L1 ) and 4, 7-di(4-substituted)-1, 10-phenanthroline (L2 –L5 ) as bidentate ligands, a series of tricarbonyl rhenium complexes, fac -Re(CO)3 (L x )Cl ( x = 1–5), were synthesized and characterized by infrared spectroscopy, 1 H NMR, 13 C NMR, and high resolution mass spectrometry. Their stereochemistry was investigated by single crystal X-ray diffraction. Theoretical highest occupied molecular orbital and lowest unoccupied molecular orbital charge distributions of fac -Re(CO)3 (L x )Cl were calculated by density functional theory calculations. Their electrochemical and electrochromic properties were studied by cyclic voltammetry, UV-vis spectroscopy and chronoamperometry. All fac -Re(CO)3 (L x )Cl complexes underwent a quasi-reversible reduction–oxidation process and an anodic peak at 1.3 V vs . Ag/Ag + . Electrochromic devices based on fac -Re(CO)3 (L x )Cl exhibited good electrochromic performance such as an obvious change in color from bleached yellow state to colored green state (a challenging electrochromic color), rapid response time of less than 3 s, moderate optical contrast and coloration efficiency, and good switching stability ( fac -Re(CO)3 (L2 )Cl retained 95.2% of its initial optical contrast after 2400 electrochromic switching cycles). The fac -Re(CO)3 (L2 )Cl with an electron-donating group (–OCH3 ) at its para -position exhibited better performance including good switching stability, a higher optical contrast and a significant change in color than the unsubstituted, –CH3 substituted, –COOCH3 substituted and Br-substituted analogues.